Evaluation of teaching methods of chemistry concepts through laboratory work: A case study of chemistry department, faculty of natural sciences, Shaheed Professor Rabbani Education University - Rahimi, Humapar Azhar; Qarizada, Deana; Stanikzai, Abdul Hadi (International Journal of Innovative Research and Scientific Studies, 2022)
This research has been carried out under the title of (Evaluation of teaching methods of chemistry concepts through laboratory work). The main objective of this research is to investigate learning and teaching methods, concepts that are taught by laboratory works and the challenges that may the teaching and learning methods face from the perspective of lecturers and students. In this research, to collect the statistical information a type of applications method and combined methods (related to library and region) has been used. In view of Cochran formula and Morgan table. The sampling method was selected systematically on random bases. In addition, the questionnaires were distributed to (136) students and (8) lecturers and their comments were collected. Based on the result of this study, researchers and lecturers have made it clear that the teaching methods of the concepts of chemistry by using laboratory works are directly related to various subjects in a complex concept, and students are taught by the activity of exploratory, exploration, problem-solving skills, and project centered. However, it can be possible in existence of sufficient materials and equipment. The majority of students and lecturers reminded the lack of laboratory, equipment and lack of knowledge of lecturers from active teaching methods of the laboratory.